Comparison of administration of estradiol valerat 1 mg and 2 mg to improve squamous epithel maturation of Pap Smear preparation on postmenopausal women - Purnamaningsih, Ika Sri (Indonesian Socety of Obstetrics and Gynecology, 2010)
Objective: To determine the most effective dose of estradiol valerat (daily oral administration of 1 mg or 2 mg for 14 days) to improve squamous epithel maturation of Pap Smear on postmenopausal women. Method: Seventy one postmenopausal women with atrophic Pap Smear were participated in this randomized double blind clinical trial. 35 subjects received estradiol valerat 1 mg and the other 36 subjects received estradiol valerat 2 mg. After daily oral administration of estradiol valerat for 14 days, second Pap Smear were performed to evaluate epithel maturation. The side effects were also evaluated in this study. Result: There were 5 subjects whom lost to follow up due to refused to perform second Pap Smear and 1 subject was drop out due to nausea. 65 subjects were included in final analysis. Estradiol valerat 2 mg was significantly more effective than estradiol valerat 1 mg in improving epithel maturation of Pap Smear preparation on postmenopausal women. There were no complain about nausea and vaginal bleeding. Leukorhea occurred more frequently in the 2 mg group. Conclusion: Daily oral administration of 2 mg estradiol valerat was more effective than estradiol valerat 1 mg in improving squamous epithel maturation of Pap Smear on postmenopausal women with minimal side effect (leukorhea). [Indones J Obstet Gynecol 2010; 34-2: 89-91] Keywords: Pap Smear, postmenopausal women, estradiol valerat, epithel maturation of Pap Smear